10
$\begingroup$

Recently, a student asked this summation $$ S= \sum_{k=0}^n \frac{{n \choose k}}{ {m + n-1 \choose k}} $$ without putting any effort. Interestingly, opening of the binomial coefficient doesn't seem to help, yet it is doable.

Use $$ {N\choose k}^{-1}=(N+1)\int_{0}^{1} x^k(1-x)^{N-k}\, dx. $$ Then $$ S= \sum_{k=0}^n \frac{{n \choose k}}{ {m + n-1 \choose k}}= (m+n) \sum_{k=0}^{n}\int_{0}^{1} {n \choose k} x^k (1-x)^{m+n-1}\, dx $$ $$\implies S=(m+n)\int_{0}^{1}\, dx~ (1-x)^{m+n-1}\sum_{k=0}^{n} {n \choose k}\left(\frac{x}{1-x}\right)^k$$ $$\implies S=(m+n)\int_{0}^{1}(1-x)^{m-1}dx=\frac{m+n}{m}.$$

The question is: How to do it otherwise?

$\endgroup$
2
12
$\begingroup$

Opening of the binomial coefficient indeed works. $$ \sum_{k=0}^n \frac{{n \choose k}}{ {m + n-1 \choose k}}\\=\frac{n!}{(m+n-1)!}\sum_{k=0}^n \frac{(m+n-k-1)!}{(n-k)!}\\=\frac{n!(m-1)!}{(m+n-1)!}\sum_{k=0}^n \frac{(m+n-k-1)!}{(n-k)!(m-1)!}\\=\frac{n!(m-1)!}{(m+n-1)!}\sum_{k=0}^n {m+n-k-1 \choose m-1}\\=\frac{n!(m-1)!}{(m+n-1)!}\sum_{k=0}^n {m+k-1 \choose m-1} $$
We know that, $$\sum_{k=0}^n {m+k-1 \choose m-1}={m-1 \choose m-1}+{m \choose m-1}+\cdots +{m+n-1 \choose m-1}={m+n \choose m}$$ Therefore, $$\sum_{k=0}^n \frac{{n \choose k}}{ {m + n-1 \choose k}}=\frac{n!(m-1)!}{(m+n-1)!}\cdot{m+n \choose m}=\frac{m+n}m$$

$\endgroup$
1
  • 2
    $\begingroup$ Great answer, in the ffourt step invoking $k \to n-k$ would have been a little better. $\endgroup$ – Z Ahmed Jun 18 at 3:51

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.